CONTRIBUTION À L’ÉVALUATION ET À LA CARTOGRAPHIE DE LA SENSIBILITÉ À L’ÉROSION HYDRIQUE DES SOLS DU SOUS BASSIN VERSANT DE L’OUED DE SAIDA (OUEST DE L’ALGÉRIE) - Djamel, Anteur; Abderrahmane, Labani; Mederbal, Khalladi; Mohamed, Gliz (European Scientific Journal, ESJ, 2014)
The sub-watershed of WadiSaidawich is a part of Macta watershed is characterized by a semiarid climate. Erratic rains, usually in stormy character, combined with anthropozoogenic pressure (deforestation, urbanization, overgrazing) cause a severe erosion. According to the National Agency of water resources, sediment yield (sediment from erosion) is estimated at 29667 t / year, which contribute to the siltation of the dam of Ouizert. This study was conducted using a Geographic Information System (GIS), allowed to characterize different areas of the sub-watershed, producing a synthetic map of the distribution of degrees of susceptibility to erosion. Indeed, Three classes of multifactorial vulnerability to water erosion were distinguished, areas with low vulnerability 40.18%; areas with medium vulnerability 24.93% and 34.88% highly vulnerable areas. Thus, classes with medium and high multifactorialvulnerability represent 60% of the area. This first mapping study is a tool to help decision makers to better manage water resources and soil and taking into account the expectations and needs of the rural population